2016
DOI: 10.4196/kjpp.2016.20.5.539
|View full text |Cite
|
Sign up to set email alerts
|

Nafamostat mesilate promotes endothelium-dependent vasorelaxation via the Akt-eNOS dependent pathway

Abstract: Nafamostat mesilate (NM), a synthetic serine protease inhibitor, has anticoagulant and anti-inflammatory properties. The intracellular mediator and external anti-inflammatory external signal in the vascular wall have been reported to protect endothelial cells, in part due to nitric oxide (NO) production. This study was designed to examine whether NM exhibit endothelium dependent vascular relaxation through Akt/endothelial nitric oxide synthase (eNOS) activation and generation of NO. NM enhanced Akt/eNOS phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Consistent with these studies, upregulated p-eNOS/NO expression was observed in FIR radiation-treated endothelial cells compared with control cells (Figures 1 and 3). In addition, our previous studies reported that Akt is involved in eNOS activation and induced NO production under different experimental conditions [25, 26]. In the present study, we found that FIR treatment significantly stimulated Akt/eNOS phosphorylation (Figures 1 and 3), which may be one of the upstream pathways for NO production.…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with these studies, upregulated p-eNOS/NO expression was observed in FIR radiation-treated endothelial cells compared with control cells (Figures 1 and 3). In addition, our previous studies reported that Akt is involved in eNOS activation and induced NO production under different experimental conditions [25, 26]. In the present study, we found that FIR treatment significantly stimulated Akt/eNOS phosphorylation (Figures 1 and 3), which may be one of the upstream pathways for NO production.…”
Section: Discussionsupporting
confidence: 72%
“…Endothelial nitric oxide synthase (eNOS), one of the three NOS isoforms (the other two isoforms are inducible NOS (iNOS), and neuronal NOS (nNOS)), is the key enzyme responsible for NO production in blood vessels. eNOS activity increases NO synthesis in HUVECs [29,30] and is activated by direct phosphorylation of Akt [31]. The Akt/eNOS pathway regulates the production of NO.…”
Section: Antihypertensive Activity Of Peptides Via the Akt/enos Pathwaymentioning
confidence: 99%
“…Beyond their anticoagulant propriety, both Gabexate and Nafamostat mesylate show anti-inflammatory effects, which could be useful in COVID-19 uncontrolled inflammation (Tay et al 2020). In particular, Gabexate mesylate decreases the production of inflammatory cytokines, such as TNF-α by attenuating NF-κB and JNK pathway activity, most probably through the proteolytic destruction of IκB (Yuksel et al 2003); Nafamostat mesylate shows an anti-inflammatory effectin vitro , where it mediates the inhibition of lipopolysaccharide-induced nitric oxide production, apoptosis, IL-6 and IL-8 production in cell cultures (Kang et al 2015;Choi et al 2016). In this context, Camostat mesylate could be also useful to reduce the production of inflammatory cytokines due to SARS-CoV2 infection.…”
Section: Approaching Therapies For Covid-19 Patientsmentioning
confidence: 99%